PENERAPAN KEGIATAN MEWARNAI GAMBAR UNTUK MENINGKATKAN MOTORIC HALUS PADA ANAK USIA 5 TAHUN DI KOBER PANORAMA - Haifa Latifah, Fany; Yasmin; Zulva, Siti (Jurnal Kesehatan An-Nuur, 2025)
Children's fine motor skills are learning to color pictures, as one of the alternative activities that lead to problem solving, coloring pictures is a very fun activity for children. This study aims to find out how the application of image coloring activities to fine motor skills in pre-school children aged 3-6 years at Tk Kober Panorama Batujajar. This research uses a descriptive design. Data collection was carried out by observation and interview process as well as fine motor instrument assessment. The results of the study convey that the child's fine motoric instrument is developing as expected with a total of 8 points with a description of the child lacking in one aspect of grasping and eye-hand coordination. The nursing action plan that the author has made to overcome the problems that exist in An. A, namely not achieving the aspects in the instrument assessment. Nursing implementation has been carried out for 2 consecutive days on An. A and carried out referring to the predetermined intervention, namely the Application of Picture coloring Activities to Fine Motor Skills in Pre-School Children by grasping the pencil correctly due to lack of concentration (not focused) using fine motor assessment instruments. Evaluation is carried out by researchers every action that has been carried out both formatively and summatively, to see whether or not it is in accordance with the results criteria that have been determined.